Facilitatory and inhibitory pain mechanisms are altered in patients with carpal tunnel syndrome - Soon, B; Vicenzino, B; Schmid, A; Coppieters, M (Public Library of Science, 2017)
Preliminary evidence from studies using quantitative sensory testing suggests the presence of central mechanisms in patients with carpal tunnel syndrome (CTS) as apparent by widespread hyperalgesia. Hallmarks of central mechanisms after nerve injuries include nociceptive facilitation and reduced endogenous pain inhibition. Methods to study nociceptive facilitation in CTS so far have been limited to quantitative sensory testing and the integrity of endogenous inhibition remains unexamined. The aim of this study was therefore to investigate changes in facilitatory and inhibitory processing in patients with CTS by studying hypersensitivity following experimentally induced pain (facilitatory mechanisms) and the efficacy of conditioned pain modulation (CPM, inhibitory mechanisms). Twenty-five patients with mild to moderate CTS and 25 age and sex matched control participants without CTS were recruited. Increased pain facilitation was evaluated via injection of hypertonic saline into the upper trapezius. Altered pain inhibition through CPM was investigated through cold water immersion of the foot as the conditioning stimulus and pressure pain threshold over the thenar and hypothenar eminence bilaterally as the test stimulus. The results demonstrated that patients with CTS showed a greater duration (p = 0.047), intensity (p = 0.044) and area (p = 0.012) of pain in response to experimentally induced pain in the upper trapezius and impaired CPM compared to the control participants (p = 0.006). Although typically considered to be driven by peripheral mechanisms, these findings indicate that CTS demonstrates characteristics of altered central processing with increased pain facilitation and reduced endogenous pain inhibition.